The Humanities of Food Sustainability: A Cultural History of Local Food Movements and Agro-biodiversity in Indonesia - Hanafi, Imam; Tan, Jaden; Lee, Ava (Journal of Humanities Research Sustainability, 2025)
Background. Indonesia’s contemporary food sustainability challenges reflect deep historical, cultural, and ecological transformations that have reshaped local food systems and agro-biodiversity. Local food movements have re-emerged as a response to the growing homogenization of diets, the erosion of indigenous agricultural knowledge, and the impact of industrial food regimes. These movements represent not only environmental initiatives but also cultural practices rooted in longstanding traditions of communal agriculture and ecological stewardship. Purpose. The research aims to analyze the cultural foundations of Indonesia’s local food movements, trace their historical development, and examine their contributions to sustaining agro-biodiversity. Method. A qualitative historical-cultural method was employed, drawing on archival materials, ethnographic accounts, visual documentation, and policy analysis. Analytical procedures included thematic coding, cultural narrative reconstruction, and cross-period comparison to map continuities and ruptures in food sustainability practices. Results. Findings show that local food movements are deeply embedded in cultural memory and collective identity, functioning as mechanisms for ecological resilience, resistance to food commodification, and revitalization of traditional crop varieties. The movements demonstrate how cultural narratives, ritual practices, and local knowledge systems actively shape community-led strategies for conserving agro-biodiversity. Conclusion. The study concludes that food sustainability in Indonesia cannot be understood solely through ecological or economic lenses; it must be grounded in cultural history and humanistic inquiry. Strengthening local food movements therefore requires integrating cultural values, historical understanding, and community agency into national food sustainability policies.